Scientific evidence-based of rice by-products for cancer prevention: chemopreventive properties of waste products from rice milling on carcinogenesis in vitro and in vivo - Bee, Ling Tan; Norhaizan, Mohd Esa (Hindawi Publishing Corporation, 2017)
Cancer is a significant global health concern affecting men and women worldwide. Although current chemopreventive drugs could inhibit the growth of cancer cells, they exert many adverse side effects. Dietary factor plays a crucial role in the management of cancers and has drawn the attention of researchers to be used as an option to combat this disease. Both in vitro and in vivo studies showed that rice and its by-products display encouraging results in the prevention of this disease. The mechanism of anticancer effect is suggested partly through potentiation of bioactive compounds like vitamin E, phytic acid, -aminobutyric acid (GABA), -oryzanol, and phenolics. Nevertheless, the bioactivity of rice and its by-products is still incompletely understood. In this review, we present the findings from a preclinical study both in in vitro and in animal experiments on the promising role of rice by-products with focus on cancer prevention.